Contact underwater explosion response of metallic sandwich panels with different face-sheet configurations and core materials. (December 2020) - Chen, Ganchao; Cheng, Yuansheng; Zhang, Pan; Liu, Jun; Chen, Changhai; Zhao, Yanjie; Wang, Haikun
Abstract: The dynamic response of polyurethane (PU) foam core sandwich panels subjected to contact underwater explosions (UNDEXs) was experimentally investigated in this paper. The investigation focused on the effect of face-sheet configurations on the deformation/failure modes and protective performance of the target sandwich panels. Special attention was paid to discussing the relative performance and intrinsic mechanisms amongst PU foam core sandwich panels and other two groups of sandwich panels with polyvinyl chloride (PVC) and aluminum (AL) foam cores. Multiple failure modes were exhibited by the post-tested specimens including petalling of the front face, fragment generation, petalling and Mode Itc of the back face, core perforation and global bending, as well as core-face debonding. Regardless of stand-off distances and core materials, a more efficient way to minimize the damage level of the target panels and the permanent deformation of witness plates is allocating more mass to the back face rather than the front one. The promising core material to resist the contact UNDEX is the PVC foam with a higher crushing strength when the impulse is relatively low. If the impulse possesses a high-level intensity enough to induce petalling failure of back faces, the AL foam with a higher perforation resistance would become the best option to avoid the generation of a back cap. Highlights: Contact underwater explosion experiments are conducted on polyurethane (PU) foam core sandwich panels. Effect of face-sheet configuration on the dynamic response of PU foam core sandwich panels is elucidated. Comparison with PVC and aluminum foam core sandwich panels is performed to facilitate the selection of core materials. Intrinsic mechanisms of divergences in failure modes and protective performance of three sandwich panels are illuminated.